Anatomical study of position of the TVT-O to the obturator nerve influenced by the position of the legs during the procedure: based upon findings at formalin-embalmed and fresh-frozen bodies - Hubka, Petr; Nanka, Ondrej; Martan, Alois; Svabik, Kamil; Zvarova, Jana; Masata, Jaromir (Archives of gynecology and obstetrics, 2011)
PURPOSE: Groin pain is one of the complications after TVT-O procedure. The aim was to examine the position and safety of the tape after TVT-O procedure. METHODS: We inserted TVT-O in 14 formalin-embalmed bodies with legs malpositioned (group 1) and in 5 fresh-frozen bodies with legs malpositioned (group 2) and in 5 fresh-frozen bodies with legs correctly positioned (group 3). After dissection distances from the branches of obturator nerve were measured. RESULTS: In group 1, the mean distance from the anterior branch of the obturator nerve was 8.6 mm on the left, 7.1 mm on the right. Mean distance from the posterior branch of the obturator nerve was 8.4 mm on the left, 8.9 mm on the right. In group 2, the mean distance from the anterior branch of the obturator nerve was 8.0 mm on the left, 8.0 mm on the right. Mean distance from the posterior branch of the obturator nerve was 5.0 mm on the left, 8.00 mm on the right. In group 3, the mean distance from the anterior branch of the obturator nerve was 24 mm on the left, 23 mm on the right. Mean distance from the posterior branch of the obturator nerve was 23 mm on the left, 23 mm on the right. Statistical analysis was performed with confirmation of significant difference between group of bodies with legs positioned correctly and other groups with malpositioned legs. CONCLUSIONS: The position of the legs is crucial for correct placement of TVT-O.
Keywords: Cadaver; Leg; Urinary Incontinence, Stress; Treatment Outcome; Humans; mrtvola; Suburethral Slings; Supine Position; Female; stresová inkontinence moči; formaldehyd; urologické chirurgické výkony; ženské pohlaví; kryoprezervace; nervus obturatorius; supinační poloha; Cryopreservation; Obturator Nerve; suburetrální pásky; lidé; bérec; Urologic Surgical Procedures; Formaldehyde; výsledek terapie